Intelligent Agrobots for Crop Yield Estimation using Computer Vision - Bini, D.; Pamela, D.; Mary I., Thusnavis Bella; Shamia, D.; Prince, Shajin (Computer Assisted Methods in Engineering and Science, 2022)
The machine vision-based autonomous intelligent robots perform precise farm tasks such as robot harvesting, weeding, pest or fertilizer spraying, monitoring, and pruning. Estimating crop yield is an essential assignment on a regional or federal scale. For a long time the estimation measures were based on the statistics from manual counting of plants in a specific zone. The computer vision algorithms have addressed the technical drawbacks of the conventional image processing techniques and established an autonomous discipline and yielded new approaches to crop planning. A method for quantitative assessment of a tomato crop has been developed in this research using color thresholding in MATLAB using the RGB color model. Converting an RGB image to a grayscale image is one of the steps involved in detecting red color in a taken image. After subtracting the two images, a median filter is employed to filter the noisy pixels to produce a two-dimensional black and white image. The bounding boxes are used to label the binary digital images to detect related components, and the parameters of the labeled regions are computed to measure the number of tomatoes in a crop. The obtained R2 correlation coefficient between the tomato berry counting algorithm and human counting was 0.98.  Furthermore, the color of each pixel in the acquired image is evaluated by examining RGB values for pixel intensities in the obtained image. The performance of the berry counting algorithm was evaluated, and the technique was determined to have a high precision and recognition ratio of 96%. The research indicates that this technique may be used to estimate the crop yield, which is helpful information for forecasting yields, planning harvest plans, and generating prescription maps for field-specific management strategies. The proposed model performed exceptionally well in estimating yield with each tomato (Solanum lycopersicum) crop.